The Effect Of Physical Education Health-Related Program For Employees (PEHPE) On Exercise Behaviour And Quality Of Work Life Among Employees In Mobarakeh Steel Company, Iran - Nazerian, Iman (2018)
This study aims at examining the effects of the Physical Education Health-Related Programme for Employees (PEHPE) on exercise behaviour and quality of work life among employees in Mobarakeh Steel Company, Iran. The survey method was used at the first stage while quasi experimental research was used at the second stage of this study. The questionnaire of Sports Needs Assessment in terms of Interest (SNAI) with the high reliability coefficient of .977 alpha was used for data collection among the randomly selected sample of 376 employees from the population of 15000 male employees in Mobarakeh Steel Company.